Your bones - Hunter, Amy (Pearson Education Harlow, 2010)
This informative text delves into the intricate world of the human skeletal system. It explores the various types of bones, their functions, and how they work together to support and protect our bodies. From the sturdy bones of the skull to the delicate bones of the hands and feet, readers will gain a deeper understanding of the essential role bones play in our daily lives. This engaging text combines clear explanations with captivating visuals to make learning about the human body both fun and informative.